Perlindungan Hukum terhadap Dokter dalam Memberikan Pelayanan Kesehatan Bagi Pasien yang Menolak Tindakan Medis yang Mengakibatkan Kematian - Adinda Eka Ramadhani (Syntax Corporation Indonesia, 2024)
This research examines the legal protection of doctors in the context of healthcare services at the Sultan Agung Islamic Hospital in Semarang, especially in situations where patients refuse emergency medical procedures recommended by doctors, which could potentially result in death. Through an empirical juridical approach, this study analyzes the applicable legal framework, hospital readiness, and factors influencing the provision of legal protection to doctors. The research findings indicate that Indonesian positive law provides a strong foundation for the legal protection of doctors, while the Sultan Agung Islamic Hospital in Semarang has demonstrated its readiness through well-established standard procedures and effective communicative approaches. However, there are still inhibiting factors such as a lack of legal awareness among medical staff and issues with medical record documentation. Therefore, this research is expected to contribute to a more comprehensive understanding of the dynamics of legal protection for doctors in the practice of healthcare services